Microstrip patch antenna: A review and the current state of the art - Mohammed, Abdullahi SB.; Kamal, Shahanawaz; Ain, Mohd Fadzil; Ahmad, Zainal Arifin; Ullah, Ubaid; Othman, Mohamadariff; Hussin, Roslina; Ab Rahman, Mohd Fariz (Institute of Advanced Scientific Research, 2019)
The mobile technology is fast-developing nowadays owing to its large impact on social life. Accordingly, there is a need to study the progress of the antenna systems as they are considered as core devices for wireless technology. The modern antenna designs allow a single element to be employed in many systems. The microstrip patch antennas are essentially considered in the advancement of the latest communication mechanisms in contrast to the conventional type because they offer the advantage of being low profile along with simple or inexpensive manufacturing procedures. In the recent four decades, extensive research has been carried out on the antenna systems. Consequently, this review paper provides a comprehensive account of the former and subsequent research achievements of the microstrip patch antennas. The various types of systems considered for comparison include millimeter-wave, broad banding, dual/multi-band or reconfigurable structure, size-reduction, compact, low profile, impedance bandwidth, high gain or linear and circular polarization applications. © 2019, Institute of Advanced Scientific Research, Inc.. All rights reserved.